QSAR analysis for the inhibition of the mutagenic activity by anthocyanin derivatives - Szewczuk, Nicolas Alejadro (2020)
Flavonoid compounds modulate the cytochrome P450 3A4 enzyme activity and inhibit the mutagenic activity of mammalian cells, preventing carcinogen activation and cellular DNA damage. In this work, the quantitative structure-activity relationships (QSAR) theory is applied to predict the cytochrome P450 3A4 inhibition constant by anthocyanin derivatives. Different freely available software calculates 102,260 non-conformational molecular descriptors. A training set of 12 compounds is used to calibrate the best univariable linear regression models, while a test set of 4 compounds is used to explore their predictive capability. The present results are compared with previously reported ones by using 3D-QSAR, thus demonstrating that the proposed topological QSAR models achieve acceptable statistical quality. The proposed model provides a prospective QSAR guide for the search of new anthocyanin derivatives possessing high or low predicted mutagenicity.